2014
DOI: 10.1039/c4fd00004h
|View full text |Cite
|
Sign up to set email alerts
|

Electron induced chemistry: a new frontier in astrochemistry

Abstract: The commissioning of the ALMA array and the next generation of space telescopes heralds the dawn of a new age of Astronomy, in which the role of chemistry in the interstellar medium and in star and planet formation may be quantified. A vital part of these studies will be to determine the molecular complexity in these seemingly hostile regions and explore how molecules are synthesised and survive. The current hypothesis is that many of these species are formed within the ice mantles on interstellar dust grains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 31 publications
(38 reference statements)
1
80
0
Order By: Relevance
“…the penetration depth for 2 keV electrons is ∼100 nm, while it may be as low as 20 monolayers for 100 eV electrons. 37,202 VUV penetration depths are similar to that of keV electrons.…”
Section: Uv Vs Electronsmentioning
confidence: 65%
“…the penetration depth for 2 keV electrons is ∼100 nm, while it may be as low as 20 monolayers for 100 eV electrons. 37,202 VUV penetration depths are similar to that of keV electrons.…”
Section: Uv Vs Electronsmentioning
confidence: 65%
“…Formamide is readily formed and the resonance like feature between 6 and 12 eV is characteristic of the synthesis by reactants prepared in a dissociative electron attachment process [71]. Similar experiments have shown that as many as 15 products can be formed by electron irradiation of pure methanol ices [72] including ethylene glycol and methyl formate whilst formamide HCONH2 is formed in irradiation of binary mixtures of ammonia and methanol ice and the simplest amino acid glycine from irradiation of a methylamine and carbon dioxide ice [73]. Thus, electron induced synthesis of simple cometary ices may be a route to formation of several of the organic species observed in surface material from comet 67P.…”
Section: Possibility Of Electron Induced Surface Chemistrymentioning
confidence: 61%
“…sugars, amino acids, aldehydes or amphiphilic molecules. [48][49][50][51] In fact, laboratory experiments simulating the UV processed ice mixtures showed that the presence of ammonia in these ices is essential for a stabilization of light aldehydes in a harsh space environment. 48 Similarly, the importance of methanol presence in astrochemical ices is critical to the production of amphiphilic molecules.…”
Section: Introductionmentioning
confidence: 99%